PERBEDAAN JARAK KEMAMPUAN MEMORY DIGIT PADA ANAK INTELLECTUAL DISABILITY SMPLB DENGAN ANAK NORMAL SMP - Romadhon, Fathurrohman Rozhi; Nugroho, Setyadi; Dwi, Windiarti (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Intellectual disability (ID) is a disturbance in thinking function due to below average intelligence. Based on matter This child intellectual disability experience disruption of level intelligence wrong the only one process Study And remember, different from child normal Which can do process Study And remember better. This study aims to determine the difference in the distance between digit memory ability scores in children with intellectual disabilities from SMPLB and normal SMP children. The sampling technique was carried out by purposive sampling with 40 child respondents with 20 Intellectual Disabilities and 20 normal children. Data The collected data will be analyzed univariately and bivariately, with the Shapiro-Wilk normality test, then the homogeneity test with the independent t-test. The results obtained in this study were that the mean score of digit memory ability in children with Intellectual Disabilities from SMPLB from 20 respondents was 12.85, while the mean score of digit memory ability in normal children from SMP from 20 respondents was 16.70. So the difference in the mean distance of the memory digit score in children with Intellectual Disabilities in SMPLB and normal children in SMP is 3.85, where the average value of children with Intellectual Disabilities in SMPLB is lower than that of normal children in SMP. There is a difference in the distance between the ability of digit memory scores in children with mild intellectual disabilities in junior high schools with special needs and normal junior high school children whose scores are below the average, with a result of 3.85. ABSTRAKIntellectual disability (ID) atau disabilitas intelektual adalah terganggunya fungsi pikir karena tingkat kecerdasan di bawah rata-rata. Berdasarkan hal ini anak intellectual disability mengalami terganggunya tingkat kecerdasan yang salah satunya proses belajar dan mengingat, berbeda dengan anak normal yang dapat melakukan proses belajar dan mengingat lebih baik. Penelitian ini bertujuan untuk mengetahui perbedaan jarak skor kemampuan memory digit pada anak intellectual disability SMPLB dengan anak normal SMP. Teknik pengambilan sampel dilakukan dengan purposive sampling dengan 40 responden anak dengan 20 Intellectual Disability  dan 20 anak normal. Data yang terkumpul akan dianalisis secara univariat dan bivariat, dengan uji normalitas shapiro-wilk, selanjutnya uji homogenitas dengan independent t-test. Hasil yang didapat dalam penelitian ini adalah mean skor kemampuan memory digit pada anak Intellectual Disability SMPLB dari 20 responden adalah 12,85, sedangkan mean skor kemampuan memory digit pada anak normal SMP dari 20 responden adalah 16,70. Jadi perbedaan jarak mean skor memory digit pada anak Intellectual Disability SMPLB dengan anak normal SMP adalah 3,85 yang dimana nilai rata-rata anak Intellectual Disability SMPLB lebih rendah daripada anak normal SMP. Terdapat perbedaan jarak kemampuan skor memory digit pada anak Intellectual Disability ringan SMPLB dengan anak normal SMP yang nilainya dibawah rata-rata didapatkan hasil 3,85.